PERTIMBANGAN HAKIM DALAM MENGABULKAN PERMOHONAN BANDING PERKARA PERDATA ANTARA ADVOKAT DAN KLIEN - Jacynda Sukma Putri, Farrely; Aldyan, Arsyad (Verstek, 2025)
This article analyzes the judge's consideration in granting the appeal request for a civil case in Decision No. 182/Pdt/2022/PT.SMG. The purpose of this article is to understand and identify the alignment of the judge's consideration with Article 16 of Law No. 18 of 2003 concerning Advocates. The research method used is normative legal research, making the nature of this research descriptive and applied with a case study approach. The legal materials were collected through library research from primary and secondary legal sources. The legal material analysis technique uses the method of syllogistic deduction. Based on the research results, it is concluded that the judge's consideration in granting the Appeal Request for Case No. 182/Pdt/2022/PT.SMG was solely based on the deadline for filing the appeal. The panel of judges did not properly consider the evidence submitted by the Appellant. The immunity rights guaranteed by Article 16 of Law No. 18 of 2003 concerning Advocates should apply in this case, and the Appellant should be protected by these immunity rights.